2016
DOI: 10.1371/journal.pone.0164757
|View full text |Cite
|
Sign up to set email alerts
|

Increased Serum Levels of IL-17A and IL-23 Are Associated with Decreased Vitamin D3 and Increased Pain in Osteoarthritis

Abstract: IntroductionOsteoarthritis (OA) is the most common type of arthritis and proinflammatory cytokines have been considered as the main etiologic factor in the pathogenesis of the disease. Serum levels of cytokines, that are associated with innate immunity and TH1 cells, have been analyzed in OA patients, however, there is limited research that profiles cytokines associated with Th17 cells and their relation to vitamin D3 and pain.Material and methodsThe sera from 131 patients with OA and 262 healthy controls were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
28
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(36 citation statements)
references
References 22 publications
6
28
1
1
Order By: Relevance
“…To assess the variable range of disease severity in cases with osteoarthritis, we studied in details the relation between interleukin-17 and disease function using WOMAC scale. The results of this study revealed significant relation between interleukin 17 and WOMAC scale, this was in agreement with [20,21]. The relation between interleukin-17 and disease severity in our cases using Lequesne et al scale also revealed a highly significant relation between them and this was in agreement with [19,22,23].…”
Section: Discussionsupporting
confidence: 89%
“…To assess the variable range of disease severity in cases with osteoarthritis, we studied in details the relation between interleukin-17 and disease function using WOMAC scale. The results of this study revealed significant relation between interleukin 17 and WOMAC scale, this was in agreement with [20,21]. The relation between interleukin-17 and disease severity in our cases using Lequesne et al scale also revealed a highly significant relation between them and this was in agreement with [19,22,23].…”
Section: Discussionsupporting
confidence: 89%
“…For a long time, OA was considered as an exclusive outcome of excess weight bear on joints. After Puenpatom and Victor (2009) have suggested for the first time that MeS may be associated with OA, multiple studies have documented a relationship between OA and MeS components (Askari et al 2016), which have led to the introduction of the term of metabolic OA (Courties et al 2017). Our findings support the notion that a metabolic factor (or factors), independent from weight, is part of the pathogenesis of OA (Askari et al 2017b).…”
Section: Discussionsupporting
confidence: 79%
“…Visfatin has been shown to induce chemotaxis and production of IL-1β, TNF-α, IL-6, co-stimulatory molecules by CD14+ monocytes, and increase the ability for alloproliferative response in lymphocytes (Askari et al 2016). It seems that serum levels of visfatin and its concentration in the synovial fluid are related to the amount of inflammation and severity of disease.…”
Section: Discussionmentioning
confidence: 99%
“…Knee OA is a combined consequence of environmental and genetic factors, while genetic factors account for nearly 50% of the risk of knee OA development [3]. Though the underlying mechanisms remain unknown, many studies have demonstrated that the occurrence of osteoarthritis is related to genetic factors, including interleukin-17 family [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%